Environmental Uncertainty, Capital Intensity, And Tax Avoidance With Managerial Ability As A Moderator - Riska Gustivani; Estralita Trisnawati; Verawati Verawati (UNIVED Press, 2025)
This research aims to examine the influence of environmental uncertainty and capital intensity on tax avoidance practices and analyze the role of managerial ability as a moderating variable in this relationship. The research was conducted on 24 property and real estate sector companies listed on the Indonesia Stock Exchange (BEI) during 2019–2023. The method used is quantitative, with panel data regression analysis and moderate regression analysis (MRA). The research results show that environmental uncertainty and capital intensity do not significantly affect tax avoidance. On the other hand, managerial ability has a positive and significant effect, which indicates that the higher the organizational ability, the higher the level of company tax compliance. However, managerial ability is not proven to moderate the relationship between environmental uncertainty and capital intensity on tax avoidance. These findings emphasize the importance of management's direct role in shaping corporate tax policy and the need to strengthen managerial capacity to improve fiscal compliance amidst the dynamics of a complex business environment.